Speckle tracking echocardiography can predict subclinical myocardial involvement in patients with sarcoidosis: A meta‐analysis. Issue 12 (15th October 2020) - Barssoum, Kirolos; Altibi, Ahmed M.; Rai, Devesh; Kumar, Ashish; Kharsa, Adnan; Chowdhury, Medhat; Thakkar, Samarthkumar; Shahid, Sara; Abdelazeem, Mohamed; Abuzaid, Ahmed Sami; Baibhav, Bipul; Parikh, Vishal; et al.
Abstract: Background: This meta‐analysis aims to evaluate the utility of speckle tracking echocardiography (STE) as a tool to evaluate for cardiac sarcoidosis (CS) early in its course. Electrocardiography and echocardiography have limited sensitivity in this role, while advanced imaging modalities such as cardiac magnetic resonance (CMR) and 18F‐fluorodeoxyglucose positron emission tomography (FDG‐PET) are limited by cost and availability. Methods: We compiled English language articles that reported left ventricular global longitudinal strain (LVGLS) or global circumferential strain (GCS) in patients with confirmed extra‐cardiac sarcoidosis versus healthy controls. Studies that exclusively included patients with probable or definite CS were excluded. Continuous data were pooled as a standard mean difference (SMD), comparing sarcoidosis group with healthy controls. A random‐effect model was adopted in all analyses. Heterogeneity was assessed using Q and I2 statistics. Results: Nine studies were included in our final analysis with an aggregate of 967 patients. LVGLS was significantly lower in the extra‐cardiac sarcoidosis group as compared with controls, SMD −3.98, 95% confidence interval (CI): −5.32, −2.64, P < .001, also was significantly lower in patients who suffered major cardiac events (MCE), −3.89, 95% CI −6.14, −1.64, P < .001. GCS was significantly lower in the extra‐cardiac sarcoidosis group as compared with controls, SMD: −3.33, 95% CI −4.71, −1.95, P < .001. Conclusion: LVGLS and GCS were significantly lower in extra‐cardiac sarcoidosis patients despite not exhibiting any cardiac symptoms. LVGLS correlates with MCEs in CS. Further studies are required to investigate the role of STE in the early screening of CS.